Software testing education. Teaching the concept of confirmation bias from a pragmatic perspective of reasoning / La formación en pruebas de software. Enseñanza del concepto de sesgo de confirmación desde la perspectiva del razonamiento pragmático - D'Angelo, Verónica (Estudios de Psicologia)
Wason's Selection Task, often used by information technology researchers, has traditionally highlighted the perceived inadequacies of software testers from a falsificationist perspective. However, a pragmatic approach to reasoning suggests that human cognition is influenced not only by logic but also by contextual factors. This perspective suggests that testers' deficiencies may arise from prioritizing information relevance over strict logical adherence. Addressing confirmation bias and contextual influences is crucial for a comprehensive understanding of the issue and for developing new testing strategies. Experiment 1 examined two thematic versions of the Wason task among computer science students, confirming enhanced performance in line with relevance theory. Experiment 2 showed students' ability to grasp falsification concepts and apply them to abstract tasks. This suggests the Wason test's value as a didactic tool for illustrating confirmation bias rather than solely assessing reasoning proficiency.